PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN KEMAMPUAN MENGHAFAL MUFRODAT BAHASA ARAB PADA SISWA KELAS III DI MADRASAH IBTIDAIYAH ISLAMIYAH KOTA MALANG - Dewi Chafidatur Rochimah; Muhammad Hanief; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
Arabic language subjects are one of the subjects taught in Madrasah Ibtidaiyah. This subject is felt as a difficult subject for students, because Arabic is not the language of conversation that we do in everyday life and Arabic is a Foreign Language.. The location of this study was conducted at MI Islamiyah, Malang, which is one of the Ibtidaiyah Madrasas located on Jl. S. Supriadi 172 L.This qualitative research shows characteristics that are quite strong, especially in the meaning of what happens in the process of learning Arabic Language material اَسْمَاءُاْلحَيَوَانَاتِ. And using the type of CAR research (Classroom Action Research).Data collection techniques include observation, interviews, and documentation. Research Subjects were Arabic Language Teachers and 32 Grade III Ibtidaiyah Islamiyah Madrasas. The research data were analyzed by reducing data, presenting data, and conclusions. Research Results The application of the Think Pair Share cooperative learning model can improve the ability to memorize Arabic Mufrodat. This is evident from the increase in the average value of students before and after the applied cooperative learning model of Think Pair Share pre-action 69%, cycle I 73% and Cycle II 100%. Keywords: Cooperative, Think Pair Share (TPS), Memorizing, Mufrodat.